1992
DOI: 10.1679/aohc.55.361
|View full text |Cite
|
Sign up to set email alerts
|

VIP-Immunoreactive Nerve Structures of the Gastrointestinal Tract in the Developing and Adult Domestic Duck.

Abstract: Summary. The first appearance and distribution of VIP-containing nerve structures were studied in the gut of embryonal, newly hatched and adult domestic ducks.Immunoreactive structures appeared in the mesenchyme of the gizzard-duodenum junction (antrum) at 5 days of incubation, and soon after diffused both cranially and caudally. Early in development, VIP-positive cell bodies were more numerous than positive fibres, appearing 3 days before the latter. Later on, the positive cell bodies decreased in number whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…and biochemical studies have demonstrated that both enzymes are portions of the same molecule, and a NADPH-drevealing histochemical method is currently being utilized to confirm nitrergic neurons (BREDT et al, 1990;DAWSON et al, 1991). In birds, VIP- (SUNDLER et al, 1979;VITTORIA et al, 1992;LOPEZ et al, 1993;KUENZEL and BLAHSER, 1994) and NOS-containing neurons (LI et al, 1994;BoRos et al, 1994;BRUNING et al, 1994;HIRAMATSU and OHSHIMA, 1994;BALASKAS et al, 1995) have been detected in several organs but never in the genital tract, at least to our knowledge. This study was thus made in order to explore the presence and distribution of VIP and NOS in the oviduct of the hen by means of histochemical and Immunohistochemical techniques.…”
Section: Recent Combined Morphologicalmentioning
confidence: 71%
“…and biochemical studies have demonstrated that both enzymes are portions of the same molecule, and a NADPH-drevealing histochemical method is currently being utilized to confirm nitrergic neurons (BREDT et al, 1990;DAWSON et al, 1991). In birds, VIP- (SUNDLER et al, 1979;VITTORIA et al, 1992;LOPEZ et al, 1993;KUENZEL and BLAHSER, 1994) and NOS-containing neurons (LI et al, 1994;BoRos et al, 1994;BRUNING et al, 1994;HIRAMATSU and OHSHIMA, 1994;BALASKAS et al, 1995) have been detected in several organs but never in the genital tract, at least to our knowledge. This study was thus made in order to explore the presence and distribution of VIP and NOS in the oviduct of the hen by means of histochemical and Immunohistochemical techniques.…”
Section: Recent Combined Morphologicalmentioning
confidence: 71%
“…These neurons have been also found to contain neuropeptides (Schultzeberg et al 1980;Korman et al 1989;Vittoria et al 1992;Bredkjaer et al 1994;Balemba et al 1998) and the NADPH-d enzyme (Fang et al 1993). Neverthless, mucosal ganglia and single neurons are considered to be ectopic from the submucous plexus (Stöhr 1934;Lassmann 1975) and the mucous plexus to be aganglionic (Schultzeberg et al 1980;Costa et al 1987;Timmermans et al 1990;Burns Fig.…”
Section: Discussionmentioning
confidence: 99%
“…the myenteric and submucous plexuses which are located between the inner circular and outer longitudinal layers of the tunica muscularis and in the tela submucosa, respectively (Ali and McLelland 1978. Bird enteric ganglion cells, moreover, have been extensively reported to contain neuropeptides and the enzyme NADPHdiaphorase (Vittoria et al 1992;Boros et al 1994;Balaskas et al 1995;Suzuki et al 1996;Mirabella et al 2000Mirabella et al , 2002. In the proventriculus, the distribution and neurochemistry of enteric ganglia have been studied in a few species of birds.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous nerves with VIP-like immunoreactivity have been found in such sphincters Gonda et aL, 1989;Daniel et al, 1989). Many authors have examined the distribution of the VIP-like immunoreactive nerves in the gastrointestinal tract of birds (Sundler et al, 1979;Vaillant et aL, 1980;Fontaine-Perus et aL, 1981;Reinecke et aL, 1981_;Saffrey et aL, 1982;Epstein et al, 1983;Vittoria et al, 1992). However, no detailed information has yet been reported on the VIPergic neurons in the gastroduodenal junction, which is likely to constrict as a sphincter.…”
Section: Introductionmentioning
confidence: 99%